2018
DOI: 10.3389/fpls.2018.00430
|View full text |Cite
|
Sign up to set email alerts
|

Protoplast-Esculin Assay as a New Method to Assay Plant Sucrose Transporters: Characterization of AtSUC6 and AtSUC7 Sucrose Uptake Activity in Arabidopsis Col-0 Ecotype

Abstract: The best characterized function of sucrose transporters of the SUC family in plants is the uptake of sucrose into the phloem for long-distance transport of photoassimilates. This important step is usually performed by one specific SUC in every species. However, plants possess small families of several different SUCs which are less well understood. Here, we report on the characterization of AtSUC6 and AtSUC7, two members of the SUC family in Arabidopsis thaliana. Heterologous expression in yeast (Saccharomyces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 132 publications
(234 reference statements)
2
57
0
Order By: Relevance
“…For instance, a questionable annotation could lead to erroneous hypothesis in the case of the ARR8 encoded gene (AT2G41310) shown in Figure 10. Another example is the case of AtSUC7, initially considered as a pseudogene (88), and recently shown to be translated in heterologous systems with functional restrictions on sucrose analogue transport (89). Here we show, for the first time, that AtSUC7 is transcribed and translated in germinated pollen and it suffers a dramatic down regulation at both transcriptional and translational levels upon heat stress ( Table 3).…”
Section: Discussionmentioning
confidence: 57%
“…For instance, a questionable annotation could lead to erroneous hypothesis in the case of the ARR8 encoded gene (AT2G41310) shown in Figure 10. Another example is the case of AtSUC7, initially considered as a pseudogene (88), and recently shown to be translated in heterologous systems with functional restrictions on sucrose analogue transport (89). Here we show, for the first time, that AtSUC7 is transcribed and translated in germinated pollen and it suffers a dramatic down regulation at both transcriptional and translational levels upon heat stress ( Table 3).…”
Section: Discussionmentioning
confidence: 57%
“…A previous study showed that AtSUC6 was a pseudogenes coding for non-functional proteins [39]. More recent work has shown that AtSUC6 is a high-affinity H +_ symporter mediating sucrose uptake [40]. The evolutionary distances between plants and yeast mean that the plant proteins may not target the correct membrane in yeast [41,42], or that they lack the essential protein modifications and do not show normal activity in a heterologous system.…”
Section: Discussionmentioning
confidence: 99%
“…As vacuolar and cytoplasmic physiology appeared to be similar in anthocyanic and non-anthocyanic cells, it is assumed that direct quenching of the fluorescence of the exogenous dye by anthocyanin is happening. This is because vacuolar anthocyanin interfered with the fluorescence of the vacuole-targeted dyes loaded through the different pathways including acid-dependent loading (acridine orange) [27], probenecid-sensitive anion transporters (carboxyfluorescein, fluorescein and monochlorobimane) [23][24][25][26] and sugar transporters (esculin) [28]. With regards to the sugar transporter-dependent uptake of esculin, this has been described in the literature as being limited in monocots [28], although the initial analysis that showed this, only grass species were tested [37].…”
Section: Discussionmentioning
confidence: 99%
“…Acridine orange loads into the vacuole as a weak acid [24], and also showed a similar reduction of fluorescence in anthocyanic cells (Figure 2g). Similarly, esculin, a fluorescent sucrose analogue that is a coumarin glucoside and that is pumped across the plasma membrane and then into the vacuole by sucrose transporters [28] also loaded into the vacuole of onion epidermal cells where it too showed less fluorescence in anthocyanic cells ( Figure 2j).…”
Section: Anthocyanic Cells Show Reduced Fluorescence Vacuolar Dyesmentioning
confidence: 99%